2002
DOI: 10.1038/sj.ejhg.5200841
|View full text |Cite
|
Sign up to set email alerts
|

The mutation spectrum of hyperphenylalaninaemia in the Republic of Ireland: the population history of the Irish revisited

Abstract: Phenylketonuric and hyperphenylalaninaemic patients in the population of the Republic of Ireland were screened for mutations at the human phenylalanine hydroxylase (PAH) locus. A composite data set for the island of Ireland was generated by merging the findings of this study with extant data for Northern Ireland. Analysis of this data on the basis of the four historic provinces (Munster, Leinster, Connacht and Ulster) revealed genetic diversity that is informative in terms of demographic forces that shaped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
14
0
2
Order By: Relevance
“…The C-to-T transition at nucleotide c.1222 involves a CpG dinucleotide, and R408W as well as other recurrent mutations are thought to have arisen by deamination of methylated cytosine [Abadie et al, 1989]. R408W-H1 (associated with haplotype 1) is largely confined to the British Isles and is found at its highest frequency in western Ireland [O'Donnell et al, 2002]; it has probably arisen in a prehistoric population of Britain or Ireland, possibly in the Neolithic period O'Donnell et al, 2002]. R408W-H2 is common throughout eastern, central, and southeastern Europe as well as Scandinavia but is rare in western and Mediterranean Europe; highest relative frequencies are found in the Baltic states.…”
Section: Pku Mutations and The History Of European Peoplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The C-to-T transition at nucleotide c.1222 involves a CpG dinucleotide, and R408W as well as other recurrent mutations are thought to have arisen by deamination of methylated cytosine [Abadie et al, 1989]. R408W-H1 (associated with haplotype 1) is largely confined to the British Isles and is found at its highest frequency in western Ireland [O'Donnell et al, 2002]; it has probably arisen in a prehistoric population of Britain or Ireland, possibly in the Neolithic period O'Donnell et al, 2002]. R408W-H2 is common throughout eastern, central, and southeastern Europe as well as Scandinavia but is rare in western and Mediterranean Europe; highest relative frequencies are found in the Baltic states.…”
Section: Pku Mutations and The History Of European Peoplesmentioning
confidence: 99%
“…Some mutations that are common in Scandinavian countries, such as F299C and Y414C, are also found (in lower frequencies) in Ireland and Britain. There is considerable variation of mutation frequencies within Ireland, as shown in Table 1 [ O'Donnell et al, 2002]. Not included in Table 1 is mutation D282N, which has a relative allele frequency of 4% in southwest England.…”
Section: Britain and Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the R408W-1.8 mutation was found to occur at high relative frequency in Ireland and neighboring populations, leading to the suggestion that Ireland had been a second center of diffusion of R408W [Treacy et al, 1993;O'Neill et al, 1994;Eisensmith et al, 1995;Zschocke et al, 1997]. More recently, it has been shown that the gradient of R408W-1.8 observed across northwestern Europe continues into Ireland and peaks in Connacht (the most westerly province), while spatial autocorrelation analysis demonstrated that the gradient is consistent with a localized cline of R408W-1.8 likely to have been established by human migration [O'Donnell et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in Ireland, the local gene pool is likely to date back to the end of the neolithic period, approximately 2500 BC. At that time, 100,000-200,000 people lived on the island [de Paor, 1986], too many for a newly introduced copy of R408W-H1 to drift to its current frequency of 0.5-0.8% [Zschocke et al, 1995;O'Donnell et al, 2002]. Even if the mutation had been highly frequent at the end of the early Irish settlement approximately 300-400 generations ago, its current frequency would FIGURE 1: Relationship after t generations between the starting frequency, q 0 , and current frequency, q t , of a strictly recessive mutation.…”
Section: Introductionmentioning
confidence: 99%